Estilos de apego y comportamiento sexual en pacientes con vih. ospital provincial General Docente Riobamba, 2018-2019 - Lisette Estefania, Barba Lara (2019)
The main objective of this investigation is to analyze the attachment styles and sexual behavior of patients with HIV at the Hospital Provincial General Docente Riobamba, period 2018-2019. This is a quantitative, bibliographic, and documentary investigation; its designs are transversal; the level is descriptive and correlational, the simple consist of 45 medical records that meet the inclusion and exclusion criteria. For data collection, observation charts used, these charts had all the personal information of patients such as sociodemographic data, adult attachment style assessment scale results, applied by the staff of mental health, and the HIV clinic of the HPGDR. Among the most evident results, 44%of the sample had a fearful attachment style, 33% had an avoidance attachment style. Patients identified as having dangerous sexual behavior. A highly significant relationship is evident between avoidance attachment styles and dangerous sexual acts with a (p<0.05), It concluded that HIV patients have sexual risky sexual practices related to attachment styles.